Increasing the Value of Coconut Blondo in Potato Flour as a Basic Ingredient for Nutrition-Rich Biscuits as an Alternative to Stunting Prevention - Koapaha, Teltje; Langi, Tineke Marlyn; Montolalu, Maya Hendrietta; Tooy, Dedie; Pinatik, Herry Frits (Budapest International Research and Critics University, 2024)
The aim of the research was to: analyze the nutritional content of biscuits made from potato starch with the addition of coconut blondo and the ornagoleptic characteristics of the panelists' liking for the biscuits. resulting from. The method used in this research is a descriptive method, with the addition of blondo treatment. The blondo addition treatment consisted of: control, 10 g, 30 g, and 50 g blondo. Each treatment was repeated 3 times. The results of the research show that the chemical characteristics of potato-based biscuits with the addition of coconut blondo are water content 2.19 - 5.01%, ash content 2.47 - 3.30%, fat content 16.29 - 24.1%, protein content 6.34 - 9.07%, carbohydrate content 60.56 - 71.59%, crude fiber 2.25 – 2.68%, and calories 458.33 - 490.56 Kcal. Organoleptic characteristics of the panelists' level of preference for biscuits made from potato flour showed that the addition of coconut blondo obtained an average color value of 4.26 – 5.76 (neutral – liked), aroma 4.06 – 5.86 (neutral – liked), taste 4.7 – 5.1 (somewhat liked), texture 4.76 – 5.46 (somewhat like – like) and crispness 4.7 – 5.56 (neutral – like). The addition of blondo to making biscuits made from potato flour in terms of nutritional content of protein and fat and calories is in accordance with SNI Biscuits and is liked by the panelists. The biscuits produced can be used as snacks for pregnant women and toddlers as an alternative to preventing stunting.